Socioeconomic inequalities in reproductive, maternal, newborn and child health in Guyana: a time trends analysis - Gary Joseph; Luis Paulo Vidaletti; Cecil Boston (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Guyana is among the countries committed to achieving the sustainable development goals. This research assessed the patterns of change in reproductive, maternal, newborn, and child health (RMNCH) in Guyana. # Methods Four nationally representative surveys conducted from 2009 to 2019 were assessed. Temporal trends in RMNCH indicators were assessed at the national level, by place of residence, and by wealth index. The slope index and concentration index of inequality were calculated to assess trends in inequalities over time. The average absolute annual change (AAAC) of the indicators was calculated using a weighted variance regression. # Results From 2006 to 2019, we observed an increase in the coverage of institutional delivery (from 82.6% to 97.7%), and exclusive breastfeeding (from 21.4% to 31.0%), among others. Likewise, antenatal care with four or more visits increased from 77.4% in 2009 to 84.7% in 2019. The opposite was observed for coverage of current contraceptive use (modern methods) (from 32.7% to 28.2%), family planning needed satisfied (from 49.6% to 43.8%), tetanus toxoid in pregnancy (from 31.7% to 8.2%) and full vaccination coverage (from 82.0% to 63.4%). Under-five stunting prevalence decreased from 18.0% to 9.2% and the under-five mortality rate from 40.4 to 29.3 per 1,000 live births. The gap between the poorest and richest women tended to decrease for seven out of the 16 intervention indicators, as well as for under-five stunting prevalence and under-five mortality rate. Institutional delivery was the best performer in increasing coverage and decreasing inequality over time, while immunization with measles was the worst performer. # Conclusions Guyana has made great progress in improving its RMNCH indicators. However, the observed decline in the coverage of several RMNCH indicators can be seen as a warning sign to redouble efforts to achieve sustainable development goals, SDGs 1 and 2, by 2030 and to reduce inequalities by lagging no one behind.